Magnetic solid‐phase extraction and spectrophotometric determination of pseudoephedrine in real samples. Issue 3 (26th January 2022) - Pourbasheer, Eslam; Fathi Majd, Sima; Azari, Zhila; Ansari, Samira; Ganjali, Mohammad Reza
Abstract: In the present study, the magnetic iron oxide nanoparticles as an efficient sorbent were successfully utilized for the investigation of pseudoephedrine in water and urine samples before spectrophotometric evaluation. Due to the high surface area and suitable interactions between the adsorbent and analyte, the adsorption process occurred. The optimization process was applied to the parameters that might have an impact on the extraction efficiencies, including the pH, sorbent quantity, salt effect, type and volume of eluent, and the contact time affecting the adsorption and desorption of the analyte. By exerting the optimum procedure, the proper linearities ranging from 1 to 30 and 1 to 24 μg/mL with good correlation coefficients of 0.999 and 0.998 enhanced for water and urine samples. This method is proved to be as accurate and precise as it is necessary to be executed for the analytical measurements, since the measured recoveries were 99 and 96.12%, with the detection limits of 0.88 and 1.003 μg/mL for water and urine samples, respectively. The obtained results indicate that the proposed method is simple, effective, and inexpensive for the measurements of pseudoephedrine in water and urine samples. Abstract : The magnetic iron oxide nanoparticles as an efficient sorbent were successfully utilized for the solid‐phase extraction of pseudoephedrine from the real samples before spectrophotometric evaluation. The obtained results indicate that the proposed method is simple, effective, and inexpensive for the measurements of pseudoephedrine in water and urine samples.